QUANTIFICATION OF RUTIN FROM AEGLE MARMELOS USING HIGH-PERFORMANCE THIN LAYER CHROMATOGRAPHY - K. Venkata Ramana Sai; V. Ranganathan; A. Vijayarajan; K. Vijayakaran; A. Elamaran; K. Kannan; M. Pooja (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Aegle marmelos, commonly known as Bael or Bengal quince, is a medicinal plant belonging to the family Rutaceae. The leaves of Aegle marmelos are rich in bioactive compounds and are traditionally used in various herbal remedies. Medicinal properties of Aegle marmelos leaves include antidiarrheal, antipyretic, ulcer healing, anti-inflammatory, antidiabetic, hypolipidemic and antioxidant activities. Rutin is a flavonoid, specifically a glycoside of quercetin extracted from leaves of bael. In the present study, the ethanolic extract of leaves of Aegle marmelos, collected from Ethno Veterinary Herbal Garden of Veterinary College and Research Institute, Orathanadu was subjected to High Performance Thin Layer Chromatography (HPTLC) to quantify rutin, a flavonoid from this plant. The study revealed that Aegle marmelos sample was found to contain rutin @ 272.2 ,ug per 100 mg of sample.